Reduced graphene oxide functionalized magnetic nanocomposites for environmental pollutant removal - Che Nan, Siti Nursyamsulbahria; Danial, Wan Hazman; Miskon, Mohd Fuad; Abd Hamid, Shafida; Mohd Salim, Rosliza; Razali, Azaima (Trans Tech Publications Ltd, 2022)
Nowadays, the excessive and uncontrolled discharge of chemicals are imposing major health threats. The demands for clean and safe water amplifies the need to develop improved technologies for environmental contaminant removal. Considering the limitations of conventional methods for contaminants removal, we have prepared magnetic iron oxide nanoparticles functionalised with reduced graphene oxide as a potential material for environmental pollutants removal. The magnetic properties in potential adsorbent materials are highly desirable due to several advantages. Among which are their large adsorptive surface area, low diffusion resistance, high adsorption capacity and fast separation in large volumes of solution. The surface functionalised magnetic iron oxide nanoparticles (MNP) were fabricated using a one-pot hydrothermal method by adding reduced graphene oxide (rGO) into the reaction system. The graphene oxide were reduced prior to the addition in the hydrothemal decomposition step. The resultant rGO-MNP nanocomposites were characterised using FT-IR, SEM and VSM to investigate the functional groups, morphology and magnetic properties, resepectively. We also demonstrated the potential of the hybridised magnetic material with hydrophobic reduced graphene oxide for environmental pollutant removal.